Endowment fund proposal for Czech universities - Vácha, Martin (2023)
University endowment funds support education in perpetuity. Known to universities in the United States, the wealthiest endowments deliver excess returns on their multi-asset investment strategies. The endowment culture is emerging in Europe. Yet, in the Czech Republic, university endowments are virtually unexplored. This thesis aims to find out to what extent would a university endowment fund be feasible in the Czech Republic. Focusing on investment principles, it seeks to figure out how they should differ from the portfolio allocation of the wealthiest university endowment funds in the United States. Based on research findings of existing endowments in the United States and Europe, the thesis discusses the feasibility of endowment funds at Czech universities. It proposes their investment strategy, governance structure and an alternative approach. The thesis concludes that to a limited extent and under certain conditions, university endowments would be feasible at Czech universities.